Functional Foods : Opportunities and Challenges for Developing Countries - Williams, Melissa; Pehu, Eija; Ragasa, Catherine (World Bank, Washington, DC, 2012)
Functional foods have been the topic of considerable interest in the food and nutrition industry for years, but the term currently lacks a common definition. A practical definition adopted here includes products, in food or drink form, that influence specific functions in the body and thereby offer benefits for health, well-being, or performance beyond their regular nutritional value. This paper first discusses the economic opportunities from functional foods, and then discusses challenges and success factors in the sector. The paper concludes that developing countries can enjoy the benefits of the functional food sector to expand options for producers and to promote growth in the sector through partnerships between research centers, private entrepreneurs, and indigenous communities.